Manx traditional songs, rhymes and chants in the repertoire of the last native Manx speakers - Broderick, George (Studia Celtica Fennica, 2019)
The following collection of Manx traditional songs and song-fragments derives from a series of scientific surveys on obsolescence in Manx Gaelic from native Manx speakers undertaken in Man between the years 1886 and 1972. These surveys involved the gathering of linguistic material, whether through phonetic notation of textual readings or questioning, formal questionnaires, and / or sound-recordings, in order to enable a phonological and morphological assessment of the state of Manx Gaelic at the time. Such material also included connected prose-texts in the form of stories and anecdotes, as well as lyric-texts consisting exclusively of traditional songs, rhymes, chants, etc., either complete or in fragmentary form. - Though it will be seen that many of the song-texts exist only in fragmentary form, this does not necessarily mean that the informant could not have given more. The reasons for this may be multiple: e.g. the unusual circumstances of the recordings. i.e., in the formal context of an interviewer-interviewee interface whereby the interviewee would likely not have been fully at ease. Nevertheless, the material available to us today is in my view sufficient to give us a good idea of what the informants could offer. - The song-texts gathered from the last native Manx speakers are brought together for the first time to enable a concise overview.
Online veröffentlicht: 2020-03-06
Gesehen am 21.08.2024